2007
DOI: 10.1021/jp070210z
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Energies and Photoabsorption Oscillator Strengths of the Rydberg Series in CF3Cl. A Linear Response and Quantum Defect Study

Abstract: Vertical excitation energies of the CF(3)Cl molecule have been obtained from a response function approach with a CC reference function to determine absolute photoabsorption oscillator strengths in the molecular-adapted quantum defect orbital formalism (MQDO). The present work covers more highly excited Rydberg states than have been experimentally reported. Assessing of the reliability of the present calculations is provided through a comparative analysis between the results of the molecule and the Cl atom. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The doubly augmented orbitals (which are used to describe the Rydberg orbitals) have been centered on the Cl atom, based on previous results obtained for the CF 3 Cl molecule. 19,27,33 Similarly to what has been obtained for the CF 3 Cl molecule, preliminary results indicated that the location of the basis set used to describe the Rydberg orbitals is of secondary importance.…”
Section: A Computational Detailssupporting
confidence: 54%
“…The doubly augmented orbitals (which are used to describe the Rydberg orbitals) have been centered on the Cl atom, based on previous results obtained for the CF 3 Cl molecule. 19,27,33 Similarly to what has been obtained for the CF 3 Cl molecule, preliminary results indicated that the location of the basis set used to describe the Rydberg orbitals is of secondary importance.…”
Section: A Computational Detailssupporting
confidence: 54%
“…For the HCFC-133a molecule, a considerable admixture of Cl (Rydberg) and C (valence) orbitals is obtained, thus masking the assignment of the Rydberg orbitals. However, accurate calculations of the energies of the 4s and 4p Rydberg states and the ionization potential (IP) of the Cl lone pair yield quantum defects that are consistent with the values obtained for the s and p series of the chlorine atom [24][25][26].…”
mentioning
confidence: 56%
“…It is important to mention that extensions of the previous calculations of 4s and 4p states [17] to include the Rydberg nd states-using, for instance, CASSCF/CASPT2 or CASSCF/ MR-CISD approaches-are computationally much more demanding, as both valence (3d) and Rydberg (4d) sets of Cl orbitals should be included in the active space, which can be justified by the fact that some of the configurations generated from the former set of d orbitals (e.g., n -3d) are likely to have lower energies than the corresponding configurations obtained from the latter set [25]. Thus, for molecules containing thirdrow elements, the use of Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of basis sets has proven reliable for the calculation of vertical excitation energies ͑VEEs͒ in a number of cases that involved Rydberg states. 67,[71][72][73][74][75] The basis set here described will be denoted as ANO1 + 4s4p2d when necessary. The 4s4p2d Rydberg AOs are reported in Table I.…”
Section: A Basis Set Descriptionmentioning
confidence: 99%